Synthesis, Characterization and Evaluation of Antimicrobial Activity of Several New N-Substituted Carbazole - Al-Majidi, Suaad M H (Al-Nahrain Journal of Science, 2018)
In this research, a series of some new compounds different heterocyclic new rings, sulfur, oxygen and nitrogen containing in structures, substituted-N-carbazole, through the prepared -chloro-N-carbazolacetaimde (1) which was prepared by two methods. The first method by treated carbazole compound with sodium hydrite in DMF at 0C to give a suspension of the sodium salt of carbazole and subsequent reaction with chloroacetyl chloride. The second method reaction carbazole compound with chloroacetyl chloride and potassium hydroxide by fusion. Then reaction compound (1) by two different ways. The first way involved direct reaction with substituted-2-aminobenzothiazole under certain conditions to give new compounds (2-8) and reaction of 5-substituted-2-amino-1,3,4-oxadiazole in the presence of potassium carbonate anhydrous to give new compounds (14-18) respectively. While the second way involved condensation compound (1) with hydrazine hydrate give the corresponding hydrazine derivative (19) which the conversion new Schiff base (20-23) were prepared through the reaction of hydrazine derivative (19) with aromatic aldehyde. Followed the cyclization of compounds (20-23) by used sodium azide in dry THF to give substituted tetrazoles (24-27) respectively. The prepared compounds identified by spectral methods [FTIR, 1H-NMR, 13C-NMR] and measurement some of its physical properties and some specific reaction, furthermore we were studied the effects of the preparing compounds on some strains of three types of bacteria and one yeast.